Resilience, values and ecosystem services: innovations in rangeland governance - Upton, Caroline, author; Dulmaa, D., author; Nyamaa, N., author; Nutag Action and Research Institute, publisher (Colorado State University. Libraries, 2015)
Mongolia's socio-ecological rangeland systems face a number of critical, contemporary challenges. Climatic change, persistent poverty and growing land use conflicts, especially around mining, pose complex problems both for herders and policy-makers. Furthermore, there is renewed emphasis on meeting Convention on Biological Diversity (CBD) and Aichi targets, following the publication of Mongolia's 5th National CBD report in March 2014, and the development of a new National Biodiversity Strategic Action Plan. (E)valuation of the contributions of rangeland ecosystem services (ES) to biodiversity and livelihoods/wellbeing are highlighted as priorities for future planning therein. ES thinking, valuation and commodification are becoming increasingly influential in other contemporary policy initiatives, not least through the development of the national REDD+ roadmap, Business and Biodiversity offset programmes and Government commitments to the ‘Green Economy'. Nonetheless critical questions remain about the ES paradigm itself, values/ valuation of ES and how these may be enacted and supported through policy. Here we report on a three year Darwin-Initiative funded project, which aimed to ‘generate policy and practice relevant knowledge of values of ecosystem services (ES) in Mongolia, and test the efficacy of Payment for Ecosystem Services (PES) schemes, in order to enhance biodiversity and livelihoods'. Aims were realised through i) participatory mapping and analysis of ES, including cultural ES, with 300 herder households across four case study sites, and the development of innovative methods for non-economic valuation; ii) co-development and implementation of a novel rangeland payment for ES (PES) scheme at the four sites, through the Plan Vivo standard; iii) analysis of the impacts ES and of the PES scheme on biodiversity and livelihoods. Methods used included deliberative valuation approaches, mapping, ranking and choice modelling to examine group and individual values and trade-offs between ES across ecologically contrasting areas. We also applied the SOLVES (Social Values of ES) GIS model to highlight spatial, place-specific dimensions of ES values, as part of a series of wider biodiversity, livelihoods and ES assessments. Results highlight spatial and temporal diversities in ES values, importance of cultural ES for wellbeing, and the potential of carefully designed PES schemes to contribute to more resilient socio-ecological rangeland systems in the future.
Presented at the Building resilience of Mongolian rangelands: a trans-disciplinary research conference held on June 9-10, 2015 in Ulaanbaatar, Mongolia.
Keywords: values; ecosystem services; livelihoods; biodiversity; governance